Prosopos in Student Communication with Generative AI: A Phenomenological Study of Persona Formation and AI Literacy in Digital Higher Education - Fery Harianto; Rajab Ritonga; Pitoyo Pitoyo (International Journal Labs, 2026)
The emergence of Generative Artificial Intelligence (AI) has significantly transformed digital communication in higher education, enabling natural language interactions that resemble interpersonal dialogue. This study investigates how students construct communicative relationships with AI and develop AI literacy in academic contexts. The research aims to explore students' experiences in assigning personas to AI, engaging in